2016
DOI: 10.3390/microorganisms4030027
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effects Triggered by Lactic Acid Bacteria Exopolysaccharides: New Insights into Molecular Interactions with Host Cells

Abstract: Researchers have demonstrated that lactic acid bacteria (LAB) with immunomodulatory capabilities (immunobiotics) exert their beneficial effects through several molecules, including cell wall, peptidoglycan, and exopolysaccharides (EPS), that are able to interact with specific host cell receptors. EPS from LAB show a wide heterogeneity in its composition, meaning that biological properties depend on the strain and. therefore, only a part of the mechanism of action has been elucidated for these molecules. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 89 publications
2
84
0
1
Order By: Relevance
“…TLR signalling pathways play crucial roles in the regulation and activation of numerous pro-inflammatory molecules. LPS is a well-known activator of TLR4 [36]; however, recent studies have shown that EPS from lactic acid bacteria can also activate TLR4, TLR2 [5] and C-type lectin signalling pathways [7]. Activation of TLR4 induced downstream MyD88-dependent and TRIFdependent (MyD88-independent) pathways, which in turn led to a cascade of activated molecules, such as NF-κB, activator protein-1 (AP-1), interferon regulatory factor 5 (IRF5) and IRF3 (type I interferons) and, finally, inflammatory cytokines [49] (Additional file 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR signalling pathways play crucial roles in the regulation and activation of numerous pro-inflammatory molecules. LPS is a well-known activator of TLR4 [36]; however, recent studies have shown that EPS from lactic acid bacteria can also activate TLR4, TLR2 [5] and C-type lectin signalling pathways [7]. Activation of TLR4 induced downstream MyD88-dependent and TRIFdependent (MyD88-independent) pathways, which in turn led to a cascade of activated molecules, such as NF-κB, activator protein-1 (AP-1), interferon regulatory factor 5 (IRF5) and IRF3 (type I interferons) and, finally, inflammatory cytokines [49] (Additional file 6).…”
Section: Discussionmentioning
confidence: 99%
“…In the cells pretreated with EPS and then infected with E. coli, the highest fold change was observed for the gene encoding CD14 (logFC of 7.87), while the gene encoding CD180 was the downregulated to the greatest extent (logFC of −4.26). The CD14 molecule is a coreceptor for bacterial LPS [32], and CD180 (also known as RP105) is a negative regulator of TLR4 [5]. The expression of these genes was also altered in the E. coli-infected cells (CD14, logFC of 5.95; CD180, logFC of −3.73) but not in the cells treated only with EPS.…”
Section: Degs Related To Innate Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Many of these studies (1226) employ bacteria that have been termed “immunobiotics,” which have been defined as probiotic strains that are able to beneficially regulate mucosal immunity (27, 28). Immunobiotics are recognized by the pattern recognition receptors of epithelial and antigen-presenting cells such as dendritic cells and macrophages, and these immunobiotics are known to beneficially regulate innate and adoptive immune responses (Figure 1C); there have been tremendous advances in the clarification of strain-specific immune regulation functions at the cellular and molecular levels (28–32). …”
Section: Introductionmentioning
confidence: 99%
“…In the review of Laiño et al, [11], the current knowledge of the health-promoting actions of EPS from probiotic bacteria with special focus on their immunoregulatory actions are summarized. In addition, the article describes the studies evaluating the molecular interactions of EPS from probiotics with intestinal epithelial cells, and highlights the role of the pattern recognition receptors and their signaling pathways in the anti-inflammatory capacities of probiotic EPS.…”
mentioning
confidence: 99%